2016
DOI: 10.1111/dme.13051
|View full text |Cite
|
Sign up to set email alerts
|

Plasma uric acid effects on glomerular haemodynamic profile of patients with uncomplicated Type 1 diabetes mellitus

Abstract: The association between higher PUA with lower GFR and lower ERPF in patients with Type 1 diabetes is driven by alterations in the estimated RA . PUA-mediated RA may be caused by increased tone or thickening of the afferent renal arteriole, which might potentiate renal injury by causing ischaemia to the renal microcirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 30 publications
6
27
0
Order By: Relevance
“…In the current cohort, significantly higher PUA levels were observed in adolescent HC compared with T1D, which is consistent with previous observations in young adults and in adolescents (7,8,22). Increased urinary glucose excretion is thought to be the key mechanism responsible for PUA lowering in patients with diabetes due to a stimulatory effect of urinary glucose on the GLUT9 isoform 2 transporter on the apical membrane of the proximal tubule, which increases uric acid excretion in in vitro studies (23).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the current cohort, significantly higher PUA levels were observed in adolescent HC compared with T1D, which is consistent with previous observations in young adults and in adolescents (7,8,22). Increased urinary glucose excretion is thought to be the key mechanism responsible for PUA lowering in patients with diabetes due to a stimulatory effect of urinary glucose on the GLUT9 isoform 2 transporter on the apical membrane of the proximal tubule, which increases uric acid excretion in in vitro studies (23).…”
Section: Discussionsupporting
confidence: 91%
“…Even in normoalbuminuric patients with T1D, Krolewski et al (25) reported that mildly elevated PUA is an independent predictor of early eGFR loss. We also recently showed that higher PUA levels within the normal range are associated with lower GFR and effective renal plasma flow and higher renal vascular resistance in an adult T1D cohort without any complications (7,8). Consistent with the previous body of work in adults, the association between higher PUA and lower eGFR was present in our even earlier adolescent cohort of otherwise healthy T1D patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations